ANALISIS UPAH MINIMUM DALAM MENINGKATKAN DISIPLIN KERJA KARYAWAN (Studi Kasus di Provinsi Jawa Barat Tahun 2024) - Ateng, Ateng Kusnandar Adisaputra (Laboratorium FEBI UIN SGD Bandung, 2024)
Pay is critical to both the existence of business and its employees. For many labourers, the only motivation to labour is the expectation of receiving compensation. This research examines how raising the minimum wage might improve worker discipline. It uses the West Java Province as a case study for 2024. Qualitative approaches and descriptive-analytical procedures are the methodologies used. sources and methods of data collecting discovered via a review of the literature. Both deductive and inductive data analysis methodologies are used to provide conceptual formulations on the influence of UMP on employee work discipline. It is anticipated that this study's findings will lead to final conclusions that will expand upon and support pertinent findings from earlier research. The findings indicate that compensation is the most difficult assignment for business and the most significant factor for employees because it indicates how much is valued by the workers, their families, and society as a whole. It's also significant for the industry since it shows how hard it works to keep its human resources committed and loyal to the sector. Employee motivation and work ethic will increase as a result of the pay increase.